Teaching and Researching Translation, Basil Hatim : book review - Wendland, Ernst R. (Old Testament essays, 2014)
Basil Hatim is Professor of Translation and Linguistics at the American University of Sharjah, UAE. He is a world-recognised theorist in translation studies and an active practitioner in English/Arabic translation. He lectures widely and has published extensively in the fields of applied linguistics, text linguistics, translation/interpreting, and teaching English to speakers of other languages (TESOL). Clearly, Hatim is a theorist who practices what he teaches, and this book gives abundant evidence of his widespread trans-disciplinary experience and expertise.